NEW DATA ON GOLD MINERALIZATION IN THE KOLYMA SECTOR OF THE PERIVOLCANIC ZONE OF THE OKHOTSK-CHUKOT VOLCANOGENIC BELT - Sidorov V.A.; Al'shevskii A.V.; Volkov A.V.; Sidorov A.A. (My University, 2004)
In the Kolyma sector of the perivolcanic zone of the Okhotsk-Chukot Volcanogenic Belt (OCVB), we have discovered manifestations of an unusual complex (gold-silver-sulfide-rare metal) mineralization that can be economically feasible in the immediate future. A rather similar mineralization was recently discovered at the Arkachan deposit in the western Verkhoyansk region and near the Carlin-type deposits in northwestern Nevada (United States). Recently, new data on this type of mineralization have been reported from the Teutedzhak ore field located in the Kolyma sector of the OCVB perivolcanic zone. According to the perivolcanic zone located along the outer boundary of the OCVB is a tectonomagmatic region of the activity of Mesozoic structures in the OCVB. The Kolyma sector is confined to two regional structures (the Ayan-Yuryakh anticlinal uplift of Mesozoic structures and the overlying OCVB). Coyright